The Mindfulness Solution - Siegel, Ronald (Tantor Media, Inc., 2019)
Mindfulness offers a path to well-being and tools for coping with life's inevitable hurdles. And though mindfulness may sound exotic, you can cultivate it-and reap its proven benefits-without special training or lots of spare time. Trusted therapist and mindfulness expert Dr. Ronald Siegel shows exactly how in this inviting guide. You'll get effective strategies to use while driving to work, walking the dog, or washing the dishes, plus tips on creating a formal practice routine in as little as twenty minutes a day. Flexible, step-by-step action plans will help you become more focused and efficient in daily life; cope with difficult feelings, such as anger and sadness; deepen your connection to your spouse or partner; feel more rested and less stressed; curb unhealthy habits; find relief from anxiety and depression; and resolve stress-related pain, insomnia, and other physical problems.